A seeded propagation of Cu, Zn-superoxide dismutase aggregates in amyotrophic lateral sclerosis - Ogawa, Mariko; Furukawa, Yoshiaki (Frontiers in Cellular Neuroscience, 2014)
Abnormal accumulation of protein inclusions in motor neurons has been known as a major pathological change in amyotrophic lateral sclerosis (ALS). Increasing numbers of proteins including mutant Cu, Zn-superoxide dismutase (SOD1) have been identified as constituents of pathological inclusions in a form of insoluble fibrillar aggregates. Notably, protein fibrillar aggregates exhibit a self-perpetuating property, which can convert a soluble native protein into insoluble fibrillar aggregates. Such “seeding reaction” of protein fibrils can accelerate the aggregation significantly and would contribute to the spread of inclusion pathologies from an affected cell to its neighboring cells in neurodegenerative diseases. In ALS, a pathological change first occurs at the site of disease onset and then propagates throughout the affected tissues in a time-dependent manner; therefore, it can be assumed that seeded aggregation may be the key factor of disease progression in ALS. In this mini review, we will briefly summarize recent studies on possible roles of a seeded aggregation of SOD1 in pathomechanism of ALS.